Młodzież poddawana wielorakiej manipulacji - Drożdż, Alojzy (Studia Pastoralne, 2026)
The publication focuses on the manipulation of today’s youth as well as of their affairs. The first area concerns multiple methods of “attracting” young people to secular culture and pseudoculture. This is caused primarily by social fashion factors. It is also a strong area of nearly complete demoralization. The second area concerns medialization of the youth. This world appears in the media as a world of “computer people” and participation in “the network”. This applies above all to Facebook. The publication refers to earlier works by Ben Mezrich and Even Baileyn. Another important element of taking control over young people today is the area of economy. The author highlights the fact, that young people enter the labour market with greater difficulties compared to the older generation. This generation is seeking for livelihood and development in their work. Changes in the area of economy are forcing young people to reject the fixed both post-Marxism, and Taylorism, since both of them are ruthless for the young people. This is mainly due to the economic manipulation to which young people are powerless.